Magnetic resonance imaging and cone beam computed tomography evaluated stafne bone cavity: Report of two cases - ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2023)
Stafne bone cavity is a rare, asymptomatic, ovoid, or round-shaped radiolucent mandibular defect detected in the posterior region of the mandible and below the inferior alveolar canal. Although Stafne bone cavity can be seen at any age, it is mostly fifth or sixth decade and more common in men. This report presents two cases of Stafne bone cavity and describes their radiologic characteristics. In both cases, cone beam computed tomography and magnetic resonance imaging were used to evaluate the borders and classification of the lesions. Magnetic resonance imaging revealed that both cases had submandibular gland content. Both patients were informed about the nature of the lesions. Clinical and radiographic follow-up of these lesions without clinical symptoms showed no radiographic changes.

Stafne kemik kavitesi, inferior alveolar kanalın altında ve mandibula posterior bölgede nadir olarak görülen, asemptomatik, oval veya yuvarlak şekilli olabilen radyolusent bir mandibula defektidir. Stafne kemik kavitesi her yaşta görülebilmesine rağmen çoğunlukla beşinci veya altıncı dekatta ve erkeklerde daha sık görülür. Bu makalede iki Stafne kemik kavitesi olgusu ve radyolojik özellikleri sunulmuştur. Lezyonların sınırları ve sınıflaması konik ışınlı bilgisayarlı tomografi (KIBT) ve manyetik rezonans görüntüleme (MRG) ile belirlenmiş ve MRG’de her iki vakada da submandibular beze ait yapılar olduğu gösterilmiştir. Hastalar lezyonların özellikleri hakkında bilgilendirilmiş ve klinik semptomları olmayan bu lezyonların klinik ve radyolojik takiplerinde herhangi bir değişiklik gözlenmemiştir.
Stafne kemik kavitesinin MRG ve KIBT ile değerlendirilmesi: İki olgu sunumu
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Diş Hekimliği (çeşitli); Dentistry (miscellaneous); cone beam computed tomography; magnetic resonance imaging; Mandible; submandibular gland; Mandibula; submandibular bez; manyetik rezonans görüntüleme; konik ışınlı bilgisayarlı tomograf; Mandible; submandibular gland; magnetic resonance imaging; cone beam computed tomography